Haji Agus Salim's Political Hermeneutical Thoughts on Islam and The State - Junaidi, Junaidi; Eman, Mulyadi; Marwan, Marwan (Dinasti Publisher, 2025)
This study examines Haji Agus Salim's political thinking on the relationship between Islam and the state in Indonesia. This study aims to examine Haji Agus Salim's political thinking on the relationship between Islam and the state in the Indonesian context. The main focus lies in exploring his concept of theo-democracy, which combines Islamic values with the principles of modern democracy in an inclusive and dynamic manner. Haji Agus Salim rejected formal theocracy and viewed the state as a moral and ethical instrument that opens up space for political ijtihad for Muslims in a pluralistic society. This study uses a descriptive qualitative approach with a systematic review method, and utilizes hermeneutic analysis to understand the socio-political context that shaped Agus Salim's thinking. Data were collected through a literature review of relevant primary and secondary documents. The results show that Agus Salim's thinking is contextual, creative, and relevant to address the challenges of the relationship between Islam and the state in various periods of Indonesian history. He also proposed the idea of Islamic socialism as an alternative to capitalism and communism, emphasizing social justice and the welfare of the people. This idea makes an important contribution to the discourse of a democratic, pluralistic, and just state. This study recommends the need for conceptual and implementational deepening of Haji Agus Salim's theo-democratic ideas as a reference in formulating inclusive state policies based on universal Islamic values.